Uncovered interest rate parity phenomenon and determinants of domestic interest rates: an analysis of Pakistan and China economies - Malik Saqib Ali; Ishtiaq Ahmad; Muhammad Faizan (Future Business Journal, 2024)
Abstract The core objective of this article is to explore the viability of uncovered interest parity and to reconnoiter major determinants of domestic interest rates of the Pakistan and China economies. It is imperative to study the interest rate parity that assistances to comprehend that exactly how exchange rate and domestic interest rate influence foreign interest rate of two economies in emerging trends in international trade. The World Development Indicators is main source of data gathering, and it ranges from 1980 to 2023 for the analysis of both models. This study considers two models, Engle–Granger causality has been applied in Model 1, to analyze the uncovered interest parity, and findings indicate that the exchange rate of each country has no effect on the interest rate of the other country. However, Model 2 investigates the main determinants of domestic interest rate and their long-run associations for Pakistan and China. To capture the long-run association, ARDL estimation technique has been deployed, and findings show the long-run relations and co-integration among the policy variables of both countries. In Pakistan, consumer price index and exchange rate hold positive linking with the domestic interest rate; however, output level is adversely correlated. The error correction term is 91%, confirming the rapidity of equilibrium adjustment when a shock occurs. Regarding the Chinese economy, consumer price index and exchange rate have a negative impact on China domestic interest rate. The results of the error correction model indicate an 80% speed of convergence in the long run. This study suggests that improvement in productivity and exchange rate may assist both economies to experience steady exchange rate and interest rate.